Implementasi Pembuatan Bantal Sebagai Upaya Pengolahan Sampah Plastik di Dusun Kebon Agung Kabupaten Sleman - Adinda Dwi Puspitasari; Nova Tia Ariyani; Greef Rose Hashina; Salma Hasna Khoirunnisa; Nanda Rochman Sucahyo; Yamtana Yamtana; Choirul Amri (JPS : Jurnal Pengabdian Serulingmas, 2023)
An environmental problem that is currently still difficult to solve is the accumulation of waste. The amount of waste which continues to increase every time can be a serious problem because it can cause environmental damage and pollution. Plastic waste is the kind of waste that is hard to compose by microorganism so its easy to pile up and causing environmental pollution. One way to overcome this problem is to recycle plastic waste. Based on observations and interview data, the residents of Kebon Agung Village didn’t have knowledge about proper plastic waste management to reduce the amount of plastic waste. Community service team held the education program of plastic waste management and training program of making pillow from plastic waste to women residents at Kebon Agung Village. The aim of these programs are to reduce the pile of plastic waste and increasing the residents’ knowledge about plastic waste management. The result of this program is the residents of Kebon Agung Village can make a pillow from plastic waste and understand the proper plastic waste management. The residents of Kebon Agung Village also experience behavior changes which is no more littering and already have the awareness to do proper plastic waste management.